Impact of High-Rise Buildings Construction Process on Adjacent Tunnels - Haifeng Guo; Aijun Yao; Jiantao Zhang; Yijun Zhou; Yanfei Guo (Advances in Civil Engineering)
The demand for buildings constructed along subway lines is increasing, and analysis of the impact of foundation excavation and building construction on adjacent tunnels is critical. This study investigated the variation law of tunnel deformation and surrounding earth pressure on an existing tunnel resulting from deep foundation excavation and the load of buildings. Four groups of scale model tests and corresponding numerical simulation calculations were conducted in four different modes: over unloading-loading, shallow-side unloading-loading, middle-side unloading-loading, and deep-side unloading-loading, which are according to the different relative position of the foundation pit and the tunnel. The results show that when the tunnel stretches across different areas, corresponding deformation occurs owing to the different mechanical mechanisms during excavation and loading. The results can provide evidence for the further study on the impact of adjacent construction process on the tunnels.